Analysis of coiling stable roll of hot-dip galvanized strip. Issue 1 (1st December 2022) - Lu, Fangtao; Lin, Zhijun; Lin, Guoli; Murong, Wei; Hu, Faqi; Li, Liejun
Abstract: The coiling stable roll of hot-dip galvanized is a defect formed in the galvanizing process. The zinc slags and floating foreign matters in the zinc pot will directly or indirectly adhere to the roll surface of the stabilizer roll with the flow of zinc liquid. When the strip steel contacts the stabilizer roll, the zinc slag will extrude and deform the iron base plate and form pits. In this paper. The causes of the defects were analyzed. There were two methods to eliminate the coiling stable roll, that is, to reduce the generation and accumulation of zinc slags in the zinc pot. The main measures are first to control the temperature of the strip entering the zinc can plate and the temperature of the molten zinc, and then control the amount of residual bottom residue before the zinc pot goes online. Another is to ensure the cleanliness of the steel strip before it enters the molten zinc. Based on this, the main measures implemented are: improving the cleaning ability of the cleaning section and improving the reducing ability during annealing to inhibit the formation and accumulation of zinc powder in the furnace head area.